2015
DOI: 10.1016/j.asmart.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic study of rotator cuff muscle activity during full and empty can tests

Abstract: The empty can (EC) and full can (FC) tests are used as diagnostic tools for patients with rotator cuff disease. However, recently concerns have been raised that these tests do not selectively activate the muscle. Therefore, the purpose of this study was to evaluate the rotator cuff muscle activation levels during the EC and FC tests in various positions using electromyography. Twelve healthy, right-handed men without shoulder complaints (mean age: 26.1 years, range: 23–35 years) were included. The tests were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Se estima que, aproximadamente por cada dos grados de elevación del húmero se genera un grado de rotación superior escapular 5 , aunque esto puede ser influenciado por: variaciones individuales 8 , cargas externas 3,9,10 , nivel de fuerza muscular 11 , posición articular 5,12 , fases de elevación 9,13,14 , velocidad del movimiento 13 ; presencia de alteraciones musculoesqueléticas 15 , y planos de elevación 12,14,16 . Utilizando electromiografía de superficie (EMGs), se ha reconocido el efecto del ángulo de elevación 6 o la rotación humeral 17,18 sobre los patrones de activación de los músculos del hombro durante la elevación. Para el caso de los planos de elevación, a nuestro saber, existen solo cuatro estudios que se ha enfocado en este punto.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Se estima que, aproximadamente por cada dos grados de elevación del húmero se genera un grado de rotación superior escapular 5 , aunque esto puede ser influenciado por: variaciones individuales 8 , cargas externas 3,9,10 , nivel de fuerza muscular 11 , posición articular 5,12 , fases de elevación 9,13,14 , velocidad del movimiento 13 ; presencia de alteraciones musculoesqueléticas 15 , y planos de elevación 12,14,16 . Utilizando electromiografía de superficie (EMGs), se ha reconocido el efecto del ángulo de elevación 6 o la rotación humeral 17,18 sobre los patrones de activación de los músculos del hombro durante la elevación. Para el caso de los planos de elevación, a nuestro saber, existen solo cuatro estudios que se ha enfocado en este punto.…”
Section: Introductionunclassified
“…Los estudios de O'Conell et al 19 e Ishigaki et al 20 se limitan a analizar únicamente la EMGs del músculo subescapular y trapecio respectivamente. Kai et al 18 , evalúan únicamente músculos del manguito rotador, pero en posiciones isométricas. Por su parte, el trabajo de Hawkes et al 21 , realiza estas comparaciones en distintos músculos del hombro, pero sin distinguir entre las distintas etapas de la elevación.…”
Section: Introductionunclassified
“…Other author showed the result of investigating the effect of simultaneous recruitment of the lower extremity muscles and trunk muscles on the serratus anterior activation when performing a forward punch plus [Kaur et al, 2014]. In the studies comparing the full can test and the empty can test, one study showed that muscle activation of supraspinatus and subscapularis was greater during the empty can test than during the full can test and one study showed there was no evidence of a difference in rotator cuff muscle activation levels between the empty can test and the full can test [Kai et al, 2015;Boettcher, Ginn, & Cathers, 2009]. A different muscle activation between scapular and coronal plane abduction was also reported [Reed, Cathers, Halaki, & Ginn, 2016].…”
Section: Introductionmentioning
confidence: 99%